Building Electoral Posters An Analytical Study of the Electoral Campaign’s Posters of the Iraqi Representative Council in 2014 - مصطفى علاء (ALBAHITH ALALAMI, 2016)
The electoral poster is the most important means and methods of the electoral campaign because of its advantages and capabilities if it is organized properly. It is an intensive propaganda message with psychological figures and semiotic connotations belonging to sub-culture. Its construction depends on a group of elements (logo, photo symbols, color and picture) and their consistency is varying from one to another. Posters must be committed the determinants of attraction, excitement, simplicity and clarity. They are working according to the following base: (fixed audience X moved recipients) and walking towards (moving X moving) due to the technical development of optical screens. These developments require double the force of the impact and enhance the attractive elements and attentions to compensate the short time of show. The research is described as a descriptive one depending on style of discourse analysis to detect the elements of electoral posters for the election of Iraqi parliament at its third season on April 30, 2014, determine their components, attempt to sensor their invisible contents using follow-up context and link them to the social space to determine their dimensions, in order to stand on the employed semiotics connotations and the approved psychological foundations, the extent of mixing structural elements in reinforcing the power of its impact to get to the controls determining electoral posters’ instruction and governed by scientific standards to raise its impact.